THE EFFECT OF RECRUITMENT AND EMPLOYEE SELECTION ON EMPLOYEE PLACEMENT AND ITS IMPACTS TOWARDS EMPLOYEE PERFORMANCE AT PT SRIWIJAYA AIR - Sarinah, Sarinah; Gultom, Rahmat Simon; Thabah, Asep Ali (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
Sriwijaya Air realizes the importance of candidates selection of process, because this process will result in employees in accordance with the prescribed qualifying so as to achieve a performance from these new employees. The purpose of this study was to determine the effect of the implementation of the recruitment and placement of employees selection and its impact on the performance of employees of Â PT Sriwijaya Air Jakarta. The analytical method used is the method of path analysis. The results showed that recruitment and selection variablesÂ  influence significantly on the placement of employees. Likewise, employee placement variable influence significantly on the performance of employees of PT Sriwijaya Air Jakarta. However, only recruitment variable that Significantly influence on employee performance. Recruitment is one - the only variable that has direct influence on employee performance. While selection and placement of employees variable do not affect the performance of employees.